Assessment of unloaded and loaded squat jump performance with a force platform: Which jump starting threshold provides more reliable outcomes? - Pérez-Castilla, A.; Rojas, F. J.; Garcia-Ramos, A. (Journal of Biomechanics, 2019)
This study aimed to explore the influence of different onset thresholds on the between-session reliability and magnitude of squat jump (SJ) performance. Twenty men were tested on two sessions separated by 48 h against external loads of 0.5, 30 and 60kg. The initiation of the jump was defined as the first instant in which the vertical ground reaction force exceeded system weight by 10 N (10 N), 50 N (50 N), 1% of system weight (1%SW), 10% of system weight (10%SW) and five standard deviation of system weight minus 30 ms (5SDSW). The following variables were calculated from the force-time signal collected on a force platform: mean, peak and time to peak values of force, power and velocity, average rate of force development, peak rate of force development, rate of force development index, impulse, jump height, and push-off time. The 50 N, 10%SW and 5SDSW thresholds generally revealed a higher reliability than the 10 N and 1%SW thresholds (97 and 21 out of 252 comparisons for the coefficient of variation and intraclass correlation coefficient, respectively). The magnitude of most of the variables calculated using the 50 N and 10%SW thresholds significantly differed with respect to the 10 N, 1%SW and 5SDSW thresholds (P < 0.05). These results suggest that both the reliability and magnitude of SJ performance variables are influenced by the jump starting threshold. The 50 N, 10%SW and 5SDSW thresholds maximise the reliability of SJ performance variables, while the 5SDSW should be recommended since it considers more force signal than the 50 N and 10%SW thresholds.